Extraction and purification of protease inhibitor(s) from seeds of Helianthus annuus with effects on Leptinotarsa decemlineata digestive cysteine protease. (January 2017) - Ashouri, Shabnam; Farshbaf Pour Abad, Reza; Zihnioglu, Figen; Kocadag, Ebru
Abstract: The aim of the current investigation was to purify cysteine protease inhibitors from sunflower ( Helianthus annuus L. cv. Record) (Asteraceae) seeds with potential activity on gut protease of Colorado potato beetle (CPB), Leptinotarsa decemlineata Say (Coleoptera: Chrysomelidae). Ammonium sulfate precipitated proteinaceous fractions; 0–30%, 30–50%, 50–70%, and 70–100% showed 41.03%, 48.66%, 41.53%, and 28.83% inhibition on the last instar larval gut general protease activity, respectively. Also, fraction 30–50% showed the highest inhibitory effect on digestive general protease activity of all developmental stages. This fraction was purified using two different chromatography techniques; ion-exchange using DEAE and affinity using SiO2 -CPB larval gut enzyme mix. Four peaks of protein were eluted from ion-exchange chromatography using NaCl step gradient. When used Z-Ala-Arg-Arg-4mßNA as cysteine protease substrates, the purification fold of first fraction was obtained 28.31, also the yield was 66.89%. Fraction of affinity chromatography obtained 26.98 purification fold and yielded 53.96%. Both of the purified protein fractions from two methods showed two similar bands in SDS-PAGE with apparent molecular mass of 14 and 15 kDa. Consequently, the high level of purification fold and yield suggest that both methods were appropriate for purification, but affinity was more specific because CPB gut enzyme was used as ligand. Graphical abstract: Highlights: Sunflower seed protein caused inhibition on Colorado potato beetle protease activity. Inhibitor protein was purified using ion-exchange chromatography by DEAE column. Inhibitor protein was purified using affinity chromatography by SiO2 as matrix. Affinity chromatography is more specific, since larval gut enzyme was used as ligand.